Impact of neutrophil–lymphocyte ratio on long-term outcome in patients with craniopharyngioma. Issue 37 (September 2018) - Zhang, Jing; He, Min; Liu, Zhiyong; Song, Yanlin; Wang, Yuelong; Liang, Ruichao; Chen, Hongxu; Xu, Jianguo
Abstract : Abstract: Neutrophil–lymphocyte ratio (NLR) is a poor prognostic factor in many tumors including glioblastoma multiforme (GBM), colorectal, and prostate cancer. The aim of this study was to investigate the prognostic value of preoperative NLR in patients with craniopharyngioma. Around 149 patients of craniopharyngioma surgically were treated at the Department of Neurosurgery, West China Hospital from January 2008 to December 2010, including 84 males and 65 females aged from 6 to 70 years were retrospectively reviewed, and preoperative NLR was analyzed. Overall survival (OS), progression free survival (PFS), and quality of life (QOL) were evaluated. The 5-year OS and PFS rates were 81.21% and 75.84%. Preoperative NLR was significantly correlated with OS (HR = 1.44, 95% CI 1.16–1.79, P = .001) and PFS (HR = 1.46, 95% CI 1.22–1.74, P < .001). The best cut-off value of NLR was found to be 4 based on the receiver operator characteristics (ROC) curve. Patients with NLR ≥4 had a significantly worse QOL ( P = .039), lower OS rate ( P = .009), and PFS rate ( P < .001). Preoperative NLR may be a simple, readily available, and valid predictor of long-term outcome in craniopharyngioma. We suggest that the NLR can provide effective guidance to neurosurgeons for more information about the tumor and prognostic evaluation.